RNA interference of the P450 CYP6CM1 gene has different efficacy in B and Q biotypes of Bemisia tabaci. Issue 8 (8th October 2014) - Li, Jingjing; Li, Xiaomin; Bai, Rune; Shi, Yan; Tang, Qingbo; An, Shiheng; Song, Qisheng; Yan, Fengming
Abstract BACKGROUND Cytochrome P450 monooxygenases have been proven to be associated with high resistance in Bemisia tabaci B biotype (Middle East–Asia Minor 1 genetic group) and Q biotype (Mediterranean genetic group) to the neonicotinoid class of insecticides. In this study, the RNA interference (RNAi) effects on P450 CYP6CM1 gene expression, mortality and pesticide‐detoxifying ability between B. tabaci B and Q biotypes were compared in an attempt to provide a basis for potential RNAi application in management of this pest. RESULTS Double‐stranded RNAs (dsRNAs) of P450 CYP6CM1 genes corresponding to the B and Q biotypes were synthesised using specific primers and introduced into the insect body of B. tabaci adults through membrane feeding. The results showed that dsRNAs significantly silenced the target genes in B. tabaci with dsRNA concentration or treatment time, and silencing was more effective in B biotype than in Q biotype. Feeding dsRNAs led to high mortality in both biotypes, with higher mortality in B biotype (up to 85.88%) than in Q biotype (up to 56.40%). In addition, ability to detoxify imidacloprid and nicotine was inhibited in dsRNA‐treated adults of both biotypes, more efficiently in B biotype than in Q biotype. CONCLUSION RNA interference of the P450 CYP6CM1 gene reduced gene expression, increased mortality, and inhibited the ability to detoxify a pesticide or a plant secondary metabolite in both biotypes of B. tabaci, with better efficacy in B biotype than in Q biotype. © 2014 Society of Chemical Industry